Liberation through reconciliation : Jon Sobrino's Christological spirituality - Valiente, O. Ernesto (Orfilio Ernesto) (Fordham University Press, 2015)
This book argues that Jon Sobrino's Christology offers the basis for a Christian spirituality of reconciliation that effectively overcomes conflict by attending to the demands of truth, justice, and forgiveness. It envisions a Christian discipleship and a theology of reconciliation inspired by Jesus' praxis and the values of God's Kingdom.